Legal Review on Online Sales Tax Collection (e-Commerce) at the Pratama Tax Office Gorontalo City - Nur Oktapiana S. Tungko (Estudiante Law Journal, 2023)
Abstract: The purpose of this paper is to identify and analyze the mechanisms for collecting online sales tax (e-commerce) as well as to identify and analyze the constraints and efforts by KPP Pratama Gorontalo in managing online sales tax (e-commerce) at the Pratama Gorontalo Tax Office. The method used in this writing is byempirical legal research methods. The results show that online merchants (e-commerce) are subject to an obligation of Value Added Tax of 11% or Value Added Tax on luxury goods from every sale made. In addition, it is subject to income tax of 0.5% of turnover which is less than 4.8 billion per year. The problem with online merchant tax management is a self-assessment system that allows traders who do not have awareness as taxpayers to register themselves and their businesses as tax objects. Existing regulations do not regulate the certainty of legal sanctions for online traders who do not fulfill tax obligations and taxpayer registration obligations for online traders. Keywords: Tax; Online Sales